Pragmatic aspects of translation of texts and oral speech on the example of the Uzbek and Russian languages. - Surmakhon Ismoilova (Genius Journals, 2022)
In modern linguistics, considerable attention is paid to the pragmatic aspect of texts and oral speech of a particular style and genre. A comprehensive study of the interaction of linguistic means and extralinguistic factors in the structure of the whole text in order to identify pragmatic functions is one of the promising directions in linguistics. The study is devoted to the study of the sources and components of the pragmatic potential of the Uzbek text and oral speech, with the help of which contact is established between the addressee and the addressee in order to exert a certain influence on him. From the diverse topics of pragmatic research, the problem of verbal (written, oral) impact on the recipient has been selected for consideration in the work. An important aspect of this problem is the study of the pragmatic aspect of Uzbek texts and oral speech.
Keywords: pragmatic aspect of texts; linguistics; contact between addressee and addressee; analysis of materials